A comparison of financial performance between Bank Islam Berhad and Public Bank Berhad from year 2005 to 2009 / Nur A’in Mohd Salim - Mohd Salim, Nur A’in (2011)
In Malaysia, there have two types of business banking they are they are Islamic banking concept and also conventional banking concept. Islamic banking has been an important role in financing and was contribute a different economics and social factors in the country, since they were introduce an Islamic banking business that were compliance with Shariah. It has been guess as competitors to the Conventional Banks. The aim of this project paper is to measure and analyze the performance of Bank Islam Berhad (Islamic Banking) and Public Bank Berhad (conventional Banks). In order to evaluate the performance of both banks, the methodologies that were use in this paper is financial ratios that divided into three ratios they are Liquidity ratios, Leverage/Solvency Ratios and Profitability ratios. In addition, the analysis were used the secondary data of annual report of each banks. This study found that the financial performances of Public Bank were more efficient, but bank Islam has increased their financial performances and both have effective management toward their assets, liabilities and also their equity. However, the finding has shown that Bank Islam were experience a better management in their financial positions even though during the economic crisis. Even so Bank Islam Berhad was having an internal problem during 2005 to 2006, its shows that Bank Islam still can survive in their banking business operations. Therefore, Bank Islam Berhad was having an advantage in term of financial management compare to Public Bank Berhad.